Establishing pregnancy specific maternal thyroid function reference intervals. (7th June 2011) - Khalid, A; Marchocki, Z; O'sullivan, R; Joyce, C; Stapleton, M; Mullane, J; O'Donoghue, K
Abstract : Thyroid disorders are common in women of childbearing age and are associated with adverse pregnancy outcomes. Physiological changes in pregnancy and the lack of pregnancy specific reference ranges make managing thyroid disorders in pregnancy challenging. Our aim was to establish trimester-specific thyroid function reference intervals throughout pregnancy, and to examine the prevalence of thyroid autoimmunity in otherwise euthyroid women. This was a prospective, cross-sectional study of low-risk pregnancies. Patients with known thyroid disorders, autoimmune disease, recurrent spontaneous abortion, hyperemesis gravidarum and pre-eclampsia were excluded. First trimester samples were obtained at the booking visit (11–14 weeks), second trimester at 18–24 weeks, and third trimester at 32–36 weeks. TFTs were analysed using the Roche Modular E170 electrochemiluminescent immunoassay. Trimester specific reference ranges (2.5th, 50th and 97.5th centiles) were calculated. In 1 year, 334 patients were recruited to the study. Median maternal age was 30 years (range 17–45). Across the trimesters, median freeT4, TSH and T3 were 14.40, 1.08 and 4.85 (first trimester); 12.80, 1.60 and 4.70 (second trimester); and 11.40, 1.59 and 4.20 (third trimester). 176 (57%) women had thyroid peroxidise antibodies detected, 25 (8%) of which were above normal range (table 1 ). We established pregnancy specific thyroid function reference intervals for our population, for use in clinical practice.